Pre-Trusted Peers Probability Influence on Eigen Trust and Reputation Model Over Peer to Peer Distributed Networks - Verma, Vinod Kumar; Singh, Surinder (International Journal of Informatics and Information Systems, 2018)
This paper investigates the impact of peer pre-trusted probability on the performance of Eigen's trust and reputation model in distributed wireless networks. Design and develop models for rigorous Eigen Trust assessment and reputation models. In addition, we evaluate our model from performance-based factors namely: accuracy, resource utilization and energy consumption. Finally, the results obtained from our investigation are suggestive of implementation for real-time distributed wireless applications. our proposal.